Confort et hygiène dans la haute société européenne (1854-1937) - Magali Lacousse (In Situ)
The French national archive service, at its Pierrefitte-sur-Seine site, holds about thirty collections left by architects, including Baltard, Labrouste, Laprade, Pouillon, Laurenti, Chemetov and Destailleur. The papers of Hippolyte Destailleur (1822-1893) and his son Walter Destailleur (1867-1940) are kept under the reference CP/536AP and are comprised essentially of architectural drawings covering the years 1854 to 1937. The examination and comparison of these drawings offer the possibility of understanding something of the criteria of hygiene and comfort deemed appropriate for the upper class in Europe. In particular, it is possible to look at bedrooms, bathrooms and lavatories and to analyse these in terms of their architecture (number of rooms, surface, position) and in social terms (separation between owners and servants). This analysis is followed by a closer examination of some representative examples, the private town houses of the Masurels, at Roubaix, the Trévarez château, the Crillon hotel and the Farnborough Hill house, in England.